YIELD OF SUNFLOWER (HELIANTHUS) DEPENDING ON THE HYBRID IN THE WESTERN FOREST-STEPPE OF UKRAINE - Bagay Т.; Lykhochvor В. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
To study the yield of sunflower hybrids in 2019–2021, field research was conducted on the experiemental field of Lviv National Environmental University. The experimental site is characterized by dark gray podzolic light loamy soil with the humus content of 2.4 %. Six hybrids of different maturity groups were studied: H4X302E, X4219, N4H470, HXK12M010, H4LM409, Camaro 2 of Nuseed company. The studies have shown that in conditions of sufficient moisture in the Western Forest-Steppe of Ukraine, sunflower hybrids (H4X302E, X4219, N4H470, HXK12M010) differed little by the main elements of yield structure. The height of plants was 175–178 cm, diameter of a basket 16.0–16.3 cm, weight of 1000 seeds – 44.1–44.7 g, number of seeds in a basket 1769–1780 pcs. The hybrid H4LM409 was characterized by the diameter of the basket increased to 17.0 cm, weight of 1000 seeds – up to 45.7 g, number of seeds in a basket – up to 1791 pcs. Much higher indicators of structural elements were provided by Camaro 2 hybrid, including plant height increased up to 183 cm, basket diameter – up to 18 cm, weight of 1000 seeds – up to 46.2 g, number of seeds in a basket – up to 1800 pcs. The relatively low yield of sunflower (2.40–2.91 t/ha) can be explained by excessive moisture in the years of research and the consequent reduction of the weight of 1000 seeds. In 2019, the yield (2.34–2.79 t/ha) decreased due to waterlogging in May, i.e. 161 mm of precipitation that was by 92 mm more comparing to the average long-term data. The lowest yield (2.28–2.72 t/ha) in 2020 was caused by excessive soil moisture during two months: 138 mm (+69 mm above the norm) of precipitation fell in May, 140 mm (+56 mm) in June. The most favorable hydrothermal conditions for formation of yield (2.58–3.22 t/ha) of sunflower hybrids were observed in 2021. The Camaro 2 sunflower hybrid produced the highest grain yield, i.e. 2.91 t/ha, that was by 0.41–0.51 t/ha higher than other hybrids. Maturity groups did not influenced the yield levels.